Entre el saber y el hacer para saber hacer. Conocimiento y prácticas en la Universidad del Norte para la buena gestión de su Ecocampus (2015)
Aware of the socio-environmental situation of the Colombian Caribbean region, the Universidad del Norte has no way out but becoming involved in the solution to face the ecological crisis that now affects this land. For this reason, the institution identifies, monitors and permanently manages the environmental impacts associated to this operation and incorporates the environmental know-how to its different educational and research processes, as well as actions to raise awareness in the institutional community. The former is integrated into the Eco-campus Uninorte program as a strategy to visualize and optimize the environmental management of the campus and increase environmental awareness through education, research and promotion in order to produce the well-being and harmonious develo-pment of the university community.The main advances of the Universidad del Norte presented in this article entail the mainstreaming of environmental knowledge into its work from the 4 areas proposed in 2014 by the XIX Forum of Ministers of Environment in Latin America and the Caribbean.The results stated derive from the revision of insti-tutional archives, theses, websites, activity reports and interviews to key environmental stakeholders of the institution and representatives of offices with environmental competence.